Factors controlling the distribution of dissolved organic carbon and nitrogen in the coastal waters off Jeju Island - Song, Young Kyoung; Kim, Jeonghyun; Oh, Yong Hwa; Joung, DongJoo; Kim, Tae-Hoon (Frontiers in Marine Science, 2023)
The composition of dissolved organic matter (DOM) in the coastal waters off Jeju Island, Korea, originates from a complex mixture of organic sources. This study examined the dynamics and sources of dissolved organic carbon (DOC) and dissolved organic nitrogen (DON) in the coastal waters off Jeju Island. Seasonal variation in the DOC and DON concentrations was observed, with significantly higher levels during summer (DOC: 82 ± 15 µM and DON: 6.8 ± 2.0 µM) than during the other seasons. In 2017, the Kuroshio Intermediate Water had a greater impact on the coastal waters off Jeju Island during winter (79%) and spring (69%) than during the other seasons, while the Changjiang Diluted Water (CDW) (12%) and the Kuroshio Surface Water (47%) had a stronger impact during summer and the Yellow Sea Cold Water (10%) had a stronger impact during autumn. Although water mass analysis provides valuable insights, certain aspects of the DOM distribution in coastal seawater remain unexplained. During summer, while the mixing of the CDW influenced the concentrations of DOC and DON, a distinct pulse in these concentrations was observed within a specific salinity range, suggesting microbial activity as a source. The relationship between dissolved inorganic nitrogen (DIN) and salinity also exhibited the opposite trend to that between DON and salinity, indicating the conversion of DON into DIN through microbial activity. These findings suggest that microbial activity plays a key role in the observed DOM pulse, transforming particulate organic matter into DOM and then converting it into DIN during the long transportation from Changjiang River to Jeju Island. This organic matter cycle could thus serve as a source of DIN in oligotrophic regions. However, further research on the sources and distribution of organic matter using biogeochemical parameters is required to gain a better understanding of the intricate processes involved.